The effects of duration to obtain a first job on mature and immature self-defense mechanisms among recent graduates - Getrude Cosmas; Patricia Joseph Kimong; Wanda Kiyah George Albert (Penerbit UMS, 2023)
Obtaining a job after graduation in today’s job market is quite challenging. Some graduates obtain a job during an internship while others do not secure their first job for a few months or even years. The length of time it takes to obtain a job might affect graduates in coping with job demands. To examine this phenomenon, a study involving 189 graduates was conducted. The study predicted that the duration of a graduate’s job search would affect their mature and immature self-defense mechanisms. The study also examined the difference between graduates with matched and mismatched jobs in using immature and immature self-defense. The study found that taking a longer time to get the first job negatively affects one’s mature self-defense, while there are no significant effects on the immature self-defense mechanism. This study showed that graduates who obtain jobs earlier after graduating tend to apply mature self-defense mechanisms (e.g., sublimation, humor, anticipation, & suppression) compared those who obtain job only after a longer duration. Regarding the differences between the two groups of graduates in using each self-defense mechanisms, the study found no significant difference. The findings showed that the mature psychological self-defense mechanism was more frequently used among graduates who get jobs sooner after graduation than among those who obtain jobs after a longer search. The study findings may help employed graduates to understand their self-defense mechanisms in adapting to their work environment based on the start of their first job.